Inclusive Learning Media Innovation in Islamic Religious Education for Students with Special Needs: Inovasi Media Pembelajaran Inklusif dalam Pendidikan Agama Islam untuk Siswa Berkebutuhan Khusus - Warohma Iftitiyani; Rustam Ibrahim (Politeknik Assalaam Surakarta, 2026)
Innovation in inclusive learning materials in Islamic Religious Education (PAI) plays a crucial role in achieving access and equality for students with special needs (ABK). Through a literature review and content analysis, this qualitative study identified three main forms of innovation. First, multisensory media such as interactive videos, prayer cards, the Talkback System, and kinesthetic activities help students understand material according to their sensory characteristics. Second, value- and emotion-based media, such as Islamic films and exemplary stories, encourage empathy, motivation, and deepened religious meaning. Third, adaptive digital media based on AI, VR, and speech-to-text and text-to-speech features enable personalized learning for each individual. However, the implementation of these innovations remains hampered by limited resources, teacher competency, and a lack of collaboration among stakeholders. These findings underscore the importance of developing an inclusive PAI media paradigm and enhancing teacher capacity through adaptive technology. Further research is needed to directly test the effectiveness of each media in inclusive classrooms, as well as to develop technology-based PAI learning models that are scalable and easily implemented across various school contexts.